Legal status at entry, economic performance, and self-employment proclivity: a bi-national study of immigrants - Amelie F. Constant; Klaus F. Zimmermann (Institute for the Study of Labor (IZA), 2005)
There are concerns about the attachment of immigrants to the labor force, and the potential policy responses. This paper uses a bi-national survey on immigrant performance to investigate the sorting of individuals into full-time paid-employment and entrepreneurship and their economic success. Particular attention is paid to the role of legal status at entry in the host country (worker, refugee, and family reunification), ethnic networks, enclaves and other differences among ethnicities for their integration in the labor market. Since the focus is on the understanding of the self-employment decision, a two-stage structural probit model is employed that determines the willingness to work full-time (against part-time employment and not working), and the choice between full-time paid work and self-employment. The choices are determined by the reservation wage for full-time work, and the perceived earnings from working in paid-employment and as entrepreneur, among other factors. Accounting for sample selectivity, the paper provides regressions explaining reservation wages, and actual earnings for paid-employment and self-employment, which provide the basis for such an analysis. The structural probit models suggest that the expected earnings differentials from working and reservation wages and for self-employment and paid-employment earnings matter much, although only among a number of other determinants. For Germany, legal status at entry is important; former refugees and those migrants who arrive through family reunification are less likely to work full-time; refugees are also less self-employed. Those who came through the employment channel are more likely to be in full-time paid work. In Denmark, however, the status at entry variables do not play any significant role. This suggests that the Danish immigrant selection system is ineffective.
Keywords: C25; F22; J15; J23; J31; J61; J82; 330; self-employment; entrepreneurship; ethinicity; migration; asylum seekers; refugees; migrant workers; family reunification; discrimination; Einwanderung; Flüchtlinge; Ausländische Arbeitskräfte; Arbeitsmarkt; Angestellte; Selbstständige; Vergleich; Deutschland; Dänemark